Enhancing Attachment of Non-Adherent Cells on Inert Surfaces - Velamoor, Sailakshmi (Auckland University of Technology, 2017)
In recent years, culturing cells on synthetic surfaces has a growing importance in many fields ranging from simple two-dimensional cell culture to biomedical applications such as tissue engineering, regenerative medicine, medical devices and biosensor chips. The extent of cell adhesion to these synthetic surfaces or biomaterials plays a decisive role in regulating the cells’ subsequent proliferation and differentiation. While a wide range of surface modification technologies are available to modify surfaces and promote cell adhesion, many are either complicated or expensive. Kode™ Technology FSL constructs have the ability to modify both cells and surfaces, and thus have the potential to be adapted to cellular adhesion. The aim of this study was to adhere proliferating non-adherent Jurkat cells to inert surfaces using Kode™ Technology. This was investigated using a biotin-streptavidin model. Findings reveal ability of FSL constructs to modify both cells and surfaces and facilitate direct adhesion in a dose dependent manner. Some cytotoxicity was observed under high insertion concentration. Although, presence of serum severely inhibits FSL insertion and retention, and cell adhesion to FSL modified surfaces, Kode™ has the potential to facilitate cellular adhesion to plastic and metal surfaces.
Keywords: FSL- biotin; Non- adherent cells; Surface modification; Kode